ضمان نجإح السياسة الاقتصادية المرتكزة على التكامل المحكم بين السياستين النقدية والمالية - محيريق, فوزي (جامعة الوادي - University of Eloued, 2014)
إن الدور المهم للسياستين المالية والنقدية، ركّزت عليه كل النظريات الاقتصادية بين مدعم لسياسة نقدية وأخرى مالية أو الدعوى لتطبيقهما والتنسيق بينهما جنبا إلى جنب؛ وذلك لما تمتلكانه، أي السياستين، من أدوات نقدية ومالية تستخدم لتصحيح أي اختلال يمكن أن يطرأ على التوازن الاقتصادي العام؛ ويظهر دور السياستين المالية والنقدية من خلال التحكم في معدلات التضخم والحد من البطالة؛ أو بصفة إيجابية توفير السلع والخدمات للمجتمع بأسعار تتناسب مع دخولهم النقدية "الاسمية"، وتوفير مناصب عمل لائقة كل حسب مستواه وتكوينه، مع ما تحققه السياستين المالية والنقدية من عدالة في توزيع الدخل والثروة. بالإضافة لجملة الأهداف الاقتصادية وغير الاقتصادية من وراء تحقيق التوازن. ذThe important role of the financial and monetary policies is the focus of all economic theories between the subsidized monetary and financial policy or the lawsuit to be applied and coordination side by side; because they possess, the two policies, monetary and financial tools used to correct any imbalance that can affect the general economic balance; The role of the fiscal and monetary policies is shown by controlling inflation and reducing unemployment; or by positively providing goods and services to the community at prices commensurate with their nominal cash income and providing decent jobs by their level and composition, Justice in the distribution of income and wealth. In addition to the range of economic and non-economic goals behind the balance
مقال
Keywords: النظريات الاقتصادية، السياسة النقدية والمالية، الاستقرار الاقتصادي; Economic theories, monetary and fiscal policy, economic stability